An Analytical Approach for Electronic Properties of Semiconductors Quantum Well Wires - Ahmad Salim Hussain Nassar (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
In this work a theoretical investigation of the electronic properties of quasi-one dimensional semiconductor systems is presented. An approximately analytical self-consistent approach is used for the calculation of the energy subbands and electron density. The electron – impurity and electron – electron interaction potentials are calculated for a two subband model, for a cylindrical quantum wire. The analytical results for the electron –impurity and electron-electron interaction potentials are in good agreement with the results of the model calculations. With my analytical results I discuss various aspects of the electronic properties of semiconductors quantum well wires, such as the binding energy of shallow impurity, screening, intrasubband Plasmon, and the mobility.